Quantification of Cigarette Smoke Particle Deposition In Vitro Using a Triplicate Quartz Crystal Microbalance Exposure Chamber. (26th December 2012) - Adamson, Jason; Thorne, David; McAughey, John; Dillon, Deborah; Meredith, Clive
Abstract : There are a variety of smoke exposure systems available to the tobacco industry and respiratory toxicology research groups, each with their own way of diluting/delivering smoke to cell cultures. Thus a simple technique to measure dose in vitro needs to be utilised. Dosimetry—assessment of dose—is a key element in linking the biological effects of smoke generated by various exposure systems. Microbalance technology is presented as a dosimetry tool and a way of measuring whole smoke dose. Described here is a new tool to quantify diluted smoke particulate deposition in vitro . The triplicate quartz crystal microbalance (QCM) chamber measured real-time deposition of smoke at a range of dilutions 1 : 5–1 : 400 (smoke : air). Mass was read in triplicate by 3 identical QCMs installed into one in vitro exposure chamber, each in the location in which a cell culture would be exposed to smoke at the air-liquid interface. This resulted in quantification of deposited particulate matter in the range 0.21–28.00  μ g/cm 2 . Results demonstrated that the QCM could discriminate mass between dilutions and was able to give information of regional deposition where cell cultures would usually be exposed within the chamber. Our aim is to use the QCM to support the preclinical ( in vitro ) evaluation of tobacco products.